An Octopus and a circle at the basis of a framework for the evaluation of sustainable mobility - Sioui, Louiselle; Morency, Catherine; Verreault, Hubert (Transport, 2018)
Worldwide, transportation authorities are keen to implement sustainable development measures and to move toward a more sustainable mobility for people and goods. However, this implementation entails a rise in the need for a sustainable development assessment framework for mobility, in order to compare different projects or to monitor a given area. This paper addresses the issue of conceptualization and standardization of the evaluation of sustainable development in transportation, by proposing a framework, which seeks to meet the various needs of transportation planners. This framework aims to provide an exhaustive view of the sustainability features (through its three main dimensions), as well as to clarify the concept of sustainability in transportation by embedding links between actions and impacts. This paper presents the basis of the framework developed as an interactive tool: (1) a representation named ‘Octopus’ categorizing the impact of mobility on the three dimensions of sustainable development and (2) a circular representation, named ‘Causal circle’, which integrates causal links between actions and impacts on these same dimensions.First published online 29 March 2016